Elektrokardiogram Monyet Ekor Panjang (Macaca fascicularis) yang Teranestesi Kombinasi Ketamin-Silasin - Deny Rahmadani; Putu Gede Yudhi Arjentinia; I Gede Soma (Udayana University, 2015)
Electrocardiograph principally is an electrical activity of heart muscle, which initiated and started by thesinoatrial node in right atrium, from which it spreads out through the all of the heart muscle. Centralnervous system influenced the strength and frequency of electrical impulse. In the anesthetized animal,heart contraction does not influenced by central nervous system. The study aimed to observe theelectrocardiogram (ECG) pattern of the wild Macaca fascicularis anesthetized by ketamine and xylazinecombination. The ECG pattern were recorded on 10 wild Macaca fascicularis during anesthetic period. Thedata were analyzed using descriptive method. The result showed that the average of the P wave was 0.04second with amplitude up to 0.10 mV; QRS complex 0.08 second and 0.36 mV; PR interval 0.13 second;QT interval 0.27 second; RR interval 14.2 mm; PR segment 0.04 second; ST segment 0.07 second;amplitude of T wave up to 0.19 mV. All of the monkeys have sinus rhythmic with average heart rate is 106beats per minute.